Pengaruh Likuiditas, Solvabilitas dan Aktivitas terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening - Sugandhi, Giovanni Vincent; Gisella, Verina; Dara, Siti Ruhana (STREAMING, 2022)
The purpose of the study was to determine the effect of liquidity, solvency and activity on firm value with profitability as intervening variables. The research population is the food and beverage companies listed on the IDX in 2016-2020. This study use quantitative methods with secondary data obtained from financial statements and use panel data. There are 23 samples from purposive sampling technique. The data analysis method is multiple regression analysis and path analysis. The results showed: liquidity have no effect on firm value, solvency have an effect on firm value, activities have an effect on firm value, liquidity have a significant effect on profitability, solvency have no effect on profitability, activity have a significant effect on profitability, profitability have an effect on firm value, profitability can mediate liquidity on firm value, profitability is not able to mediate solvency on firm value, and profitability can mediate activity on firm value.